MENCIPTAKAN KESEMPATAN BELAJAR DI TENGAH PANDEMI COVID 19 MELALUI GERAKAN LITERASI - Rabi’ah Rabi’ah; Raudlatul Jannah; Achmad Baidawi; Fadilah Fadilah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
The global problem that has been faced by society today is corona virus which is known as Covid-19. This pandemic forced some changed includes in education sector. The social distancing policy caused the learning through virtual. Unfortunately, the students who live in rural area can’t study. It because some reason includes the students have limited facilities. Therefore, this PKM gives opprtunity to the studentsto learn through some programs. The method of this research is Participatory Action research (PAR) which includes some procedurs such as planning, implementing, and evaluation. The research instruments are observation, interview and documentation. The result of the study were excellent class, writing class and teenager group discussion where are these programs provide chance for students to study during Covid-19.